Inszenierte Geschichte = Staging History Medialität und Politik europäischer Hochschuljubiläen von 1850 bis heute | Anniversaries in European Institutions of Higher Learning from 1850 to the Present - Guhl, Anton; Hürlimann, Gisela (Medien der Geschichte, 2021)
Anniversaries and jubilees play a central role in the "doing" of history. They qualitatively and quantitatively expand the group of people who consume and produce "history," while different history media correspond and compete with each other. Celebrations and ceremonies, plays and productions address individual and collective identities and (re)produce a sense of belonging to (imagined) communities.